Moon - Bauer, Marion Dane (Ready-to-read. Star reader!, 2021)
"Everyone loves Earth's little neighbor: the Moon! It lights up our night sky, guides our oceans, and so much more. Beginning readers will love learning all about the Moon in this new Level 1 Ready-to-Read"--